Manajemen Perubahan Dalam Pendidikan Islam: Study Analisis Manajemen Perubahan Perspektif QUR’AN Di SMP IT AL - Arjuna Arjuna; Nuri Aslami (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Humans in every step of their life will always experience changes, both intentional and unintentional changes. From the time he was in his mother's womb until he was born and grew up to be an adult human being and even an old man, because change is the true nature of humans as creatures. Likewise with institutions or organizations, changes will not be separated from institutions or organizations. The progress and change of an organization will be heavily dominated by the role of a leader. The ideal leader will certainly be able to bring conditional, targeted and appropriate changes to the institution he leads. Changes that are made and managed in a structured and systematic manner, will bring the led institution to achieve the goals to be achieved, to the maximum. It Al Ihya Middle School Private School is an Islamic educational institution that has the figure of a school principal as a leader who is responsible for the continuity of the learning process in the Islamic boarding school he leads. This study used aqualitative research method whose results were described descriptively, and chose SMP IT AL IHYA which was under the leadership of Mr. Amansyah as the object of research.